2021
DOI: 10.2147/dmso.s238419
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on the Role of Very-Low-Energy Diets in the Treatment of Obesity and Type 2 Diabetes in Youth

Abstract: In both developed and developing countries, pediatric obesity and type 2 diabetes are an increasing public health concern: globally 5.6% of girls and 7.8% of boys aged ≥5 years have obesity. The incidence of type 2 diabetes has increased in youth in recent decades and disproportionately affects those from ethnic/racial minority groups and disadvantaged backgrounds. For the treatment of both conditions, conventional lifestyle intervention is frequently ineffective, access to bariatric surgery is very limited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“… 160 Data on VLEDs in the treatment of youth with early onset type 2 diabetes are limited to a small pilot study 161 and a medical chart review, 162 however, they have shown early short-term success and the possibility of reducing the requirement for medication, including insulin, and inducing remission of diabetes. 163 However, there is need for further research. 163 Variations in macronutrient distribution have been widely studied due to hypothesised effects on satiety, particularly higher protein (20–30% of energy intake from protein) approaches and very low carbohydrate diets (<50g per day or <10% energy from carbohydrate) aiming to induce ketosis.…”
Section: Managementmentioning
confidence: 99%
“… 160 Data on VLEDs in the treatment of youth with early onset type 2 diabetes are limited to a small pilot study 161 and a medical chart review, 162 however, they have shown early short-term success and the possibility of reducing the requirement for medication, including insulin, and inducing remission of diabetes. 163 However, there is need for further research. 163 Variations in macronutrient distribution have been widely studied due to hypothesised effects on satiety, particularly higher protein (20–30% of energy intake from protein) approaches and very low carbohydrate diets (<50g per day or <10% energy from carbohydrate) aiming to induce ketosis.…”
Section: Managementmentioning
confidence: 99%
“…Box 4 provides summary recommendations for nutrition management, noting that there is little evidence for one specific macronutrient approach in young adult type 2 diabetes. Of interest, the very low energy diet approach has shown benefit among adolescents with obesity and newly diagnosed type 2 diabetes, but evidence for long term effects is lacking at present 26,27 . Similarly, in adults using a weight management program incorporating a low energy formula diet, the DiRECT trial achieved remission of diabetes in almost half of the patients randomised to this intervention 28 .…”
Section: Recommendationsmentioning
confidence: 99%
“…Of interest, the very low energy diet approach has shown benefit among adolescents with obesity and newly diagnosed type 2 diabetes, but evidence for long term effects is lacking at present. 26,27 Similarly, in adults using a weight management program incorporating a low energy formula diet, the DiRECT trial achieved remission of diabetes in almost half of the patients randomised to this intervention. 28 Although young adults with type 2 diabetes were not well represented in this trial and evidence for durability of effect is still limited, the approach merits further consideration given the potential pre-conceptual, occupational and other benefits of inducing remission in this age group.…”
Section: Dietary Management and Physical Activity As First Line Therapymentioning
confidence: 99%
“…It is also linked to other cardiovascular diseases such as atherosclerosis which leads to life-threatening situations (Kachur et al 2017). Lifestyle alteration is a key strategy used to tackle obesity and long-term KDs or verylow-energy diets have already been explored as a promising treatment strategy (Gow et al 2021;Kumar et al 2021).…”
Section: D-3hb and Cardiometabolic Healthmentioning
confidence: 99%